Fluid continuity equation simulation: Monitoring fluid reservoir volume in the heart over time - Olivia Maftukhaturrizqoh; Agung Dwi Wijaya; Iftita Ida Sofia; Mohtar Yunianto (Science, Technology, and Communication Journal, 2024)
Fluid flowing in a cross-section of a channel follows the law of continuity, namely the mass rate of fluid entering will be the same as the mass rate of fluid leaving. One of the applications of fluid flow is in human blood flow. Blood flow is controlled by the heart which functions to pump blood to and from the heart. The flow of blood entering and leaving the heart is determined by the cross-sectional area of the channel and the speed of blood flow through the heart. The speed of blood flow in the heart consists of two speeds, namely the systolic speed when blood leaves the heart and the diastolic speed when blood enters the heart. So that the volume in the heart can be observed changes over time. By creating a simulation using the MATLAB programming language, the difference between normal heart volume and problematic heart volume can be known. A program called reservoir and cardiac based on graphical user interface was created to determine the volume of fluid in the reservoir at any time and compare the volume of fluid in normal and abnormal hearts concerning time in 1 systole-diastole cycle.